Implementasi Yudas 1:17-25 Bagi Pertumbuhan Remaja Kristen - Ayu Niken Waoma; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The main concepts in this chapter, namely, keeping oneself in God's love, praying in the Holy Spirit, and waiting for God's grace, are analyzed to understand their impact on Christian teenagers' character, identity, and faith development. The results show that the implementation of these concepts positively affects the way Christian teenagers view themselves, their relationship with God, and their attitude toward the future. A strong hope in God's grace becomes an important pillar in their spiritual growth. Research on the implementation of Jude 1:17-25 for the growth of Christian teenagers can be carried out using qualitative research methods. This method allows the researcher to go deep into the understanding and experience of Christian teenagers related to the verse. The concept of